2016
DOI: 10.1038/mi.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Gut mucosal DAMPs in IBD: from mechanisms to therapeutic implications

Abstract: Endogenous damage-associated molecular patterns (DAMPs) are released during tissue damage and have increasingly recognized roles in the etiology of many human diseases. The inflammatory bowel diseases (IBD), ulcerative colitis (UC) and Crohn's disease (CD), are immune-mediated conditions where high levels of DAMPs are observed. DAMPs such as calprotectin (S100A8/9) have an established clinical role as a biomarker in IBD. In this review, we use IBD as an archetypal common chronic inflammatory disease to focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 263 publications
(290 reference statements)
3
83
0
1
Order By: Relevance
“…Data presented in our studies demonstrate that IL-33 is a key modulator during innate and adaptive immune responses in the development of IBD. Although an increased IL-33 expression was elicited by the colonic inflammation, we think that IL-33 exerts as a negative feedback mechanism in inflammation caused by TNBS [3, 18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data presented in our studies demonstrate that IL-33 is a key modulator during innate and adaptive immune responses in the development of IBD. Although an increased IL-33 expression was elicited by the colonic inflammation, we think that IL-33 exerts as a negative feedback mechanism in inflammation caused by TNBS [3, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology and etiology of IBD are not fully understood and the treatment options for these diseases are quite limited. To dissect the mechanism and develop novel therapeutic strategies for IBD, various kinds of animal models have been established [3]. Trinitrobenzene sulfonic acid (TNBS)-induced experimental colitis characterized by a predominant Th1/Th17-mediated immune response and mucosal inflammation which closely resembles important immunological and histopathological aspects of CD [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the paucity of data regarding intestinal fibrosis, IL-1α is considered a profibrotic cytokine, as IL-1α depletion or deficiency reduced collagen deposition and expression of fibrosis-associated genes in bleomycin-induced lung fibrosis and in models of liver fibrosis [76,77]. IL-33 is another DAMP that is released upon epithelial or endothelial injury and its role in fibrosis has not been adequately studied [78]. Epithelial-derived IL-33 has been found to promote regulatory T cell responses and to antagonize IL-23 in experimental colitis [79].…”
Section: From Endothelial and Epithelial Injury To Myofibroblast Actimentioning
confidence: 99%
“…Previous studies reported that high levels of DAMPs were detected in serum, fecal or mucosa of IBD patients as well as mice models (5255). In addition, it was demonstrated that the regulation of IBD progression by DAMPs was majorly through several approaches: (1) affecting epithelial barrier function; (2) binding with pattern-recognition receptors (PRRs) to exert directly pro-inflammatory effect; and (3) assisting in antigen-presenting cells to regulate T cells function (56). Since DAMPs are highly relevant to IBD, it is extremely essential to monitor the release pattern of these molecules.…”
Section: The Roles Of Autophagy In Ibdmentioning
confidence: 99%